Biomimetic Mechanically Enhanced Carbon Nanotube Fibers by Silk Fibroin Infiltration. Issue 19 (31st March 2021) - Yin, Zhe; Liang, Xiaoping; Zhou, Ke; Li, Shuo; Lu, Haojie; Zhang, Mingchao; Wang, Haomin; Xu, Zhiping; Zhang, Yingying
Abstract: Natural materials, such as silk, nacre, and bone, possess superior mechanical properties which are derived from their unique hierarchical structures. Individual carbon nanotubes (CNTs) are considered as one of the strongest materials. However, macroscopic CNT fibers usually have breaking strength far below that of individual CNTs. In this work, by mimicking the structure of natural silk fibers, strong and stiff CNT fibers are prepared by infiltrating silk fibroin (SF) into CNT fibers. There are abundant hydrogen bonds in SF, contributing to the enhanced interactions between neighboring CNTs. Glycerol is selected to promote the formation of β‐sheet conformation in SF, leading to further enhanced strength and modulus. Remarkably, the SF infiltrated CNT fibers show breaking strength of 1023 MPa, toughness of 10.3 MJ m −3, and Young's modulus of 81.3 GPa, which are 250%, 132%, and 442% of the pristine CNT fibers. The structure of the SF and the interactions between CNTs and SF are studied via Fourier transformed infrared spectroscopy and molecular dynamics simulation. Mimicking the hierarchical structures of natural silk fibers and enhance the interfacial load transfer by infiltrating SF are effective for reinforcing CNT fibers, which may be useful in the design and preparation of other structural materials. Abstract : By mimicking the structure of natural silk fibers, strong and stiff carbon nanotube (CNT) fibers are prepared through infiltrating silk fibroin (SF) into CNT fibers to enhance the mechanical properties of CNT fibers. The weak van der Waals force interactions are replaced by strong hydrogen bonds in SF to enhance the load transfer between neighboring CNTs.